2021
DOI: 10.1038/s41586-021-04056-3
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic circuits for independent control of prefrontal signal and noise

Abstract: Interactions between the mediodorsal thalamus and the prefrontal cortex are critical for cognition. Studies in humans indicate that these interactions may resolve uncertainty in decision-making1, but the precise mechanisms are unknown. Here we identify two distinct mediodorsal projections to the prefrontal cortex that have complementary mechanistic roles in decision-making under uncertainty. Specifically, we found that a dopamine receptor (D2)-expressing projection amplifies prefrontal signals when task inputs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 40 publications
7
80
2
Order By: Relevance
“…Interactions between thalamus and prefrontal cortex are important in dealing with perceptual uncertainty during decision making 82 . Two separate pathways may exist for this, with low-signal-related uncertainty (as would be expected with reduced bottom-up sensory input) resolved by dopaminergic projections from medial thalamus that increase prefrontal output 83 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between thalamus and prefrontal cortex are important in dealing with perceptual uncertainty during decision making 82 . Two separate pathways may exist for this, with low-signal-related uncertainty (as would be expected with reduced bottom-up sensory input) resolved by dopaminergic projections from medial thalamus that increase prefrontal output 83 .…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between thalamus and prefrontal cortex are important in dealing with perceptual uncertainty during decision making 82 . Two separate pathways may exist for this, with low-signal-related uncertainty (as would be expected with reduced bottom-up sensory input) resolved by dopaminergic projections from medial thalamus that increase prefrontal output 83 . Interestingly, changes in thalamic resting state functional connectivity 84 , as well as changes in thalamocortical effective connectivity 85 may also underlie hallucinations during exposure to LSD, consistent with a more general role for changes in thalamic connectivity in hallucinations in other contexts 86 .…”
Section: Discussionmentioning
confidence: 99%
“…Work in mice has shown that thalamocortical projections are critical for encoding cognitive functions that are affected in schizophrenia. For instance, reciprocal activity between the mediodorsal nucleus of the thalamus and the prefrontal cortex is required for maintenance of spatial working memory, cognitive flexibility, adaptive decision making, and sustaining attentional control in rodents ( Bolkan et al, 2017 ; Schmitt et al, 2017 ; Alcaraz et al, 2018 ; Rikhye et al, 2018a ; Mukherjee et al, 2021 ). However, the role of these thalamocortical circuits in cognitive symptoms has yet to be established in mouse models of 22q11DS or other schizophrenia-associated CNVs.…”
Section: Schizophrenia-risk Genes and Mechanisms Of Thalamic Dysfunctionmentioning
confidence: 99%
“…The role of uncertainty in cognition has been investigated under different assumptions and frameworks ( Grupe and Nitschke, 2013 ; Hasson, 2017 ; Peters et al, 2017 ; Mukherjee et al, 2021 ; Walker et al, 2021 ). In learning processes, uncertainty has a direct relationship with statistical and parametric learning, in that the latter aims to find patterns of consistent associations over separate experiences, while the modulation of the former directly affects the latter via predictive processes ( Hasson, 2017 ).…”
Section: Introductionmentioning
confidence: 99%